Identifikasi Bahaya Dan Penilaian Resiko Terhadap Pencegahan Kecelakaan Dan Kesehatan Kerja Pada PT Indotirta Suaka - Virgilius Ruru; Elva Susanti (LPPM Universitas Putera Batam, 2020)
Health and Safety (K3) is one of the problems that occur in the company. Occupational accidents usually occur because of factors of the workers themselves or the work environment. Occupational safety is a primary means of preventing work accidents which may result in injury or injury, defects or death, property loss, equipment or machinery damage and extensive environmental damage. Preventing accident can know the risk, one of them through Hazard Identification, Risk Assessment, and Risk Control (HIRARC). PT Indotirta Suaka is a company engaged in pig farming. The purpose of this study is to determine the factors that dominate and the level of occupational risk that is in the department of production phase 4, data collection is done by secondary data tracking, observation, and in-depth interviews of the workforce . Risk assessment result of all potential hazard known risk value and risk percentage that is low (low risk) as 7 risk category (33%), medium risk 14 risk category (67%), while for high risk (high risk ) There are 3 potential hazards to be kicked in pigs, 2 potential dangers of pigs, 2 potential poisoning hazards, 2 potential dangers hazardous, 2 potential for falling hazards from altitude, and 2 potential dangers trampled and all dominantly classified as risk Medium (medium risk). Risk control is done by Administration Control, and Use of Personal Protective Equipment (PPE)